2011
DOI: 10.2223/jped.2114
|View full text |Cite
|
Sign up to set email alerts
|

Atopy risk factors at birth and in adulthood

Abstract: Objective: To study the association between atopy and variables such as weight, length, and socioeconomic level at birth and in young adulthood.Methods: A total of 2,063 subjects were investigated in a prospective birth cohort study of individuals born in Ribeirão Preto, Brazil, in 1978Brazil, in /1979, and examined at the age of 23-25 years. Skin prick tests (SPT) for eight common allergens in Brazil were performed. Subjects with a wheal reaction ≥ 3 mm to one or more of the eight allergens tested were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…Male toddlers (63.4%) were found to be about twice as likely (odds ratio of 2.072; p = 0.03) than female toddlers to develop atopic diseases up to the age of three ( Table 1 and Table 4 ). The male gender has previously been identified as a genetic and lifestyle risk factor in the development of atopy [ 53 , 54 ]. Ferraz et al [ 53 ] and Moore et al [ 54 ] investigated the risk of the male gender in relation to atopic dermatitis and sensitization to a number of allergens, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male toddlers (63.4%) were found to be about twice as likely (odds ratio of 2.072; p = 0.03) than female toddlers to develop atopic diseases up to the age of three ( Table 1 and Table 4 ). The male gender has previously been identified as a genetic and lifestyle risk factor in the development of atopy [ 53 , 54 ]. Ferraz et al [ 53 ] and Moore et al [ 54 ] investigated the risk of the male gender in relation to atopic dermatitis and sensitization to a number of allergens, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The male gender has previously been identified as a genetic and lifestyle risk factor in the development of atopy [ 53 , 54 ]. Ferraz et al [ 53 ] and Moore et al [ 54 ] investigated the risk of the male gender in relation to atopic dermatitis and sensitization to a number of allergens, respectively. Similar studies also found males to be more susceptible to asthma in childhood than females [ 55 , 56 ], possibly because male children have a smaller airway in portion to their lung size than with females, making them more sensitive to infections and airborne triggers [ 57 ], in turn leading to greater sensitivity to aeroallergens [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another study indicated that poor fetal growth may reduce the risk of skin prick test reactivity during childhood 17. Considering the childhood period, decreasing risks of asthma, rhinitis and allergic sensitisation in 4-year-old children have been found with increasing socioeconomic position, something that may influence dietary patterns 35.…”
Section: Discussionmentioning
confidence: 98%
“…Catch-up growth may also be more predictive of childhood asthma than birth weight and length, which have otherwise been associated with such diseases 14 15. One study found an association between restricted growth in late gestation and an increased rate of later development of an atopic phenotype, whereas another found contrasting results 16 17. Similarly, anthropometric measures pointing to growth that is slower than normal in the prepubertal period, such as low adult leg length, leg : trunk ratio and total height, have been linked to higher rates of coronary heart disease, diabetes and mortality, although to lower rates of non-smoking-related cancers 18–23…”
Section: Introductionmentioning
confidence: 99%
“…Among these environmental factors are pollution, nutrition, exposure to allergens, socioeconomic level, and family size. However, there is no evidence to associate these factors with atopic phenotypes in epidemiological studies 17 .…”
Section: Discussionmentioning
confidence: 99%